Test anxiety and academic performance: A correlational study among nursing college students - Benjamin, Lizy Sonia; Mohammed, Kawther Eltayeb Ahmed (Palembang MediRose Publisher, 2023)
Background: Test anxiety is defined as an individual’s response to stimuli associated with their experiences in testing or evaluative situations. Objective: This study aims to investigate the relationship between test anxiety and the academic performance of nursing college students. Methods: We conducted a descriptive correlational study, selecting a sample of 98 nursing students through convenient sampling at a selected nursing college in Kerala, India. Data were collected using various tools, including a background variable proforma, a proforma for evaluating the academic achievement of nursing students, and the Westside Test Anxiety Scale. Results: Our findings revealed a statistically significant negative correlation (r=-0.4) between test anxiety and academic performance (p<0.05). This suggests that reducing test anxiety can lead to an improvement in academic performance. Conclusions: There is a need to plan psychological interventions aimed at reducing test anxiety and enhancing the academic performance of students. These interventions should be integrated at the policy level of academic performance management.